Host plant resistance and cultural strategies for bean stem maggot management - Ampofo, James Kwasi O. (International Center for Tropical Agriculture, 1993)
Various control tactics are being studied for incorporation in an overall strategy for the management of bean stem maggot (Ophiomyia spp.) in beans. These include host plant resistance, cultural practices and chemical pesticides. Moderate sources of resistance have been identified and these are in use in breeding programmes to incorporate resistance in local varieties. An evaluation of various cultural methods such as earthing-up, mulching and increased fertility indicate that mulching of field plots reduced plant mortality from BSM attack by 38 percent compared to the control and that mulching combined with increased soil fertility reduced plant mortality even further. Foliar application of certain botanical pesticides such as alcohol extract of neem seed powder and aqueous extract of Tephrosia leaves also reduced infestation by bean stem maggot and increased yields. Field evaluations of the use of these and other tactics in an integrated system in small scale farmers` situation are now underway.